Secondary teachers' instructional practices on argumentation in the context of science and religious education - Park, Wonyong; Erduran, Sibel; Guilfoyle, Liam (International journal of science education, 2022)
Argumentation is widely recognised as a core practice of science, but the relation between argumentation in the teaching of science in contrast to the teaching of other school subjects has not been sufficiently addressed. In this study, we investigate science and religious education (RE) teachers' instructional practices related to argumentation in lower secondary lessons in England. Through qualitative analysis of a pair of science and RE teachers' instructional practices, we characterise how the teachers participating in a professional development project understand and teach argumentation. Data sources included questionnaires, lesson materials, classroom video recordings, and written teacher reflections. Findings suggest that both teachers recognised the value of argumentation in their subject, but some variations existed in the nuances of their views and particularly how different instructional strategies were utilised to achieve the lesson goals related to argumentation. The study highlights the teachers' different understandings and enactments of argumentation as a disciplinary practice and an instructional objective in science and RE lessons. We call for further consideration of argumentation in different school subjects and how argumentation can enrich science teaching in interdisciplinary contexts.